Design and construction of a self sustainable lunar colony with in-sity resource utilisation - Toklu, Yusuf Cengiz; Järvsträt, Niklas (Swets en Zeitlinger B.V., 2003)
Recent work in an international consortium on putting down the requirements of a sustainable lunar colony has indentified seven major processes which are living, food production and life support, mining and processing, power and transport, simple manufacture, complex manufacture and construction. These processes are obviously strongly interlinked. Among these seven processes, construction is by far the most mass intensive one, considering all work areas and shelters necessary for any activities to be carried out for long periods. It will be executed in lunar environment as a multidisciplinary branch of technology to fulfill the environments of the difficult conditions. In this work the basic concerns of lunar construction industry are discussed and the differences compared to the terrestrial industry are stressed.
Proceedings of the 10th ISPE International Conference on Concurrent Engineering: Research and Applications, Advanced Design, Production and Management Systems --
Keywords: Building materials; Condition monitoring; Environmental testing; Food products; Lunar missions; Manufacture; Masonry construction; Mining; Soil testing; Structural design; Sustainable development; Lunar design; Terrestrial construction industries; Moon bases